'Brothel of the Pacific': Syphilis and the Urban Regulation of Laikini Wahine in Honolulu, 1855–75. Issue 1 (2nd January 2020) - Kindell, Christopher
ABSTRACT: By 1860, Hawai'i's Indigenous population had declined by 75 per cent when compared to its estimated pre-contact level. Legislators and physicians attributed this crisis to the seasonal migration of Hawaiian prostitutes. After contracting syphilis from sailors in Honolulu, these women returned to their Native villages where they unwittingly spread the disease. Drawing on legislation, health reports, and newspapers, this article underscores the urban-rural nature of Hawai'i's syphilis epidemic by analyzing the 1860 Act to Mitigate the Evils and Diseases Arising from Prostitution (ATM). The law compelled prostitutes to enlist on a government registry, undergo medical inspections, and submit to treatment if infected. Arresting depopulation, adherents argued, hinged on the government's ability to police Indigenous women within a conspicuous urban environment. In designing and enacting the ATM, legislators and physicians characterized Honolulu as a syphilitic breeding ground that catalyzed Indigenous depopulation by sheltering transient carriers of this highly gendered disease.